1994
DOI: 10.1111/j.1471-0528.1994.tb13557.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe factor X deficiency and successful pregnancy

Abstract: Case reportA 22 year old Asian primigravida, known to have severe factor X deficiency with a factor X level 4 % of normal activity (normal range 50-150 YO), booked for antenatal care at 12 weeks of gestation. Her parents were first cousins and two siblings were heterozygous carriers of the factor X deficiency trait. Her husband had a normal factor X level. Factor X deficiency was first diagnosed in 1983 when she presented with prolonged bleeding from cuts. She also suffered from menorrhagia and was given fresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 3 publications
0
39
0
1
Order By: Relevance
“…The coagulation parameters in our patient had improved during pregnancy when compared to non-pregnant levels. Konje et al 8 reported a case of FX deficiency which was complicated by recurrent retro placental bleeding in the antenatal period which was managed conservatively by the use of BPL factor IXA (composition per unit: 500 IU factor X, 500 IU ant thrombin III, 550 IU factor IXA, 600 IU factor II and 5000 IU Heparin). Kumar & Mehta 9 reported four pregnancies in one woman with FX deficiency, theorizing that prophylactic clotting factor replacement was instrumental in the favorable pregnancy outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The coagulation parameters in our patient had improved during pregnancy when compared to non-pregnant levels. Konje et al 8 reported a case of FX deficiency which was complicated by recurrent retro placental bleeding in the antenatal period which was managed conservatively by the use of BPL factor IXA (composition per unit: 500 IU factor X, 500 IU ant thrombin III, 550 IU factor IXA, 600 IU factor II and 5000 IU Heparin). Kumar & Mehta 9 reported four pregnancies in one woman with FX deficiency, theorizing that prophylactic clotting factor replacement was instrumental in the favorable pregnancy outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The haematoma remained stable during the follow‐up, and the patient was delivered by c‐section at 34 weeks due to preterm labour . The third case (FX 0.02 IU/mL) presented with a retroplacental haematoma diagnosed on ultrasound scan at 22 and 34 weeks, and the patient had a successful delivery by c‐section at 39 weeks for foetal distress . The fourth case (FX 0.1 IU/mL) presented with vaginal bleeding at 6 and 13 weeks.…”
Section: Antenatal Complicationsmentioning
confidence: 99%
“…Because treatment with high doses or prolonged administration of prothrombin complex concentrates rich in FX increases the risk of thromboembolism and disseminated intravascular coagulation, it is not recommended that the FX activity is raised more than 50% [2]. However, there are specific prothrombin complex concentrates containing antithrombin III and heparin as prophylaxis against thromboembolism [7].…”
Section: Discussionmentioning
confidence: 99%
“…The patient should receive an initial dose of 15-20 ml/kg body weight, followed by 3-6 ml/kg every 24 h. The rationale for such therapy is that the biological half-life of FX is 40 h. Also, prothrombin complex concentrates rich in FX have been used [2]. These concentrates are now the preferred therapy because they are virally inactivated, and the risk of volume overload during treatment is less compared with FFP [7]. Because treatment with high doses or prolonged administration of prothrombin complex concentrates rich in FX increases the risk of thromboembolism and disseminated intravascular coagulation, it is not recommended that the FX activity is raised more than 50% [2].…”
Section: Discussionmentioning
confidence: 99%